2016
DOI: 10.1136/acupmed-2015-010962
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Patients with Lumbar Spinal Stenosis: A Randomised Pilot Trial

Abstract: NCT01987622.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…28 Studies in which pain was secondary to specific disorders (eg, lumbar spinal stenosis) were also excluded. 29 Therefore we were able to reduce the heterogeneity of both the intervention and participants. We strictly assessed the RoB and took it into consideration when assessing the quality of the evidence.…”
Section: Discussionmentioning
confidence: 99%
“…28 Studies in which pain was secondary to specific disorders (eg, lumbar spinal stenosis) were also excluded. 29 Therefore we were able to reduce the heterogeneity of both the intervention and participants. We strictly assessed the RoB and took it into consideration when assessing the quality of the evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies measured functional disability: 4 used the ODI to measure disability outcomes, 18,22,25,35 and the others used the RMDQ. 23,24,30…”
Section: Functional Disabilitymentioning
confidence: 99%
“…The effect of acupuncture, compared to the control treatment, on the treatment of function limitation was À1.74 at immediate-term follow-up (95% CI À2.04 to À1.44, I 2 59.8%, moderate-quality evidence; Figure4A, including 7 studies and 761 patients),18,[22][23][24]30,35,37 À0.89 at short-term follow-up (95% CI À1.15 to À0.62, I 2 0%, highquality evidence; Figure4B, including 4 studies and 244…”
mentioning
confidence: 99%
“…Another trial conducted in China demonstrated [26] that the decrease in the mean value of the leg pain intensity NRS score in the EA group was 4.65 ± 6.37 at week 4, which was higher than the value of 2.30 (1.86–2.75) obtained in our trial at the same time point. In a pilot trial comparing EA with physical therapy for symptomatic lumbar spinal stenosis (LSS) [27], pain in the back and leg showed small improvements at 3 months. However, the ODI scores were different from the scores obtained in our study.…”
Section: Discussionmentioning
confidence: 99%